Burden attributable to child maltreatment in Australia. (October 2015) - Moore, Sophie E.; Scott, James G.; Ferrari, Alize J.; Mills, Ryan; Dunne, Michael P.; Erskine, Holly E.; Devries, Karen M.; Degenhardt, Louisa; Vos, Theo; Whiteford, Harvey A.; McCarthy, Molly; Norman, Rosana E.
Abstract: Child maltreatment is a complex phenomenon, with four main types (childhood sexual abuse, physical abuse, emotional abuse, and neglect) highly interrelated. All types of maltreatment have been linked to adverse health consequences and exposure to multiple forms of maltreatment increases risk. In Australia to date, only burden attributable to childhood sexual abuse has been estimated. This study synthesized the national evidence and quantified the burden attributable to the four main types of child maltreatment. Meta-analyses, based on quality-effects models, generated pooled prevalence estimates for each maltreatment type. Exposure to child maltreatment was examined as a risk factor for depressive disorders, anxiety disorders and intentional self-harm using counterfactual estimation and comparative risk assessment methods. Adjustments were made for co-occurrence of multiple forms of child maltreatment. Overall, an estimated 23.5% of self-harm, 20.9% of anxiety disorders and 15.7% of depressive disorders burden in males; and 33.0% of self-harm, 30.6% of anxiety disorders and 22.8% of depressive disorders burden in females was attributable to child maltreatment. Child maltreatment was estimated to cause 1.4% (95% uncertainty interval 0.4–2.3%) of all disability-adjusted life years (DALYs) in males, and 2.4% (0.7–4.1%) of all DALYs in females in Australia in 2010. Child maltreatment contributes to a substantial proportion of burden from depressive and anxiety disorders and intentional self-harm in Australia. This study demonstrates the importance of including all forms of child maltreatment as risk factors in future burden of disease studies.